Z Taśmoteki Rozgłośni Polskiej RWE. Rozmowa Konrada Tatarowskiego z Józefem Garlińskim - Tatarowski, Konrad; Garliński, Józef (Archiwum Emigracji, 2013)
FROM THE TAPE COLLECTION OF THE POLISH SECTION OF RADIO FREE EUROPE. KONRAD TATAROWSKI’S INTERVIEW WITH JÓZEF GARLIŃSKI The conversation between Konrad Tatarowski and the writer and émigré historian, Józef Garliński, who died in London in the year 2005, has took place in mid October 1991 and has been played in fragments during the broadcast “Polish artists in exile” in RFE on the 9th and 16th of November 1991. The talk has a biographic-informational character, alludes to the authors memories of youth, to his life during the II World War, to the circumstances of living in Poland and to his literary, historical and journalistic work during the post-war period.